PENGARUH MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE PICTURE AND PICTURE TERHADAP HASIL BELAJAR PPKN SISWA KELAS IV SDN KADUJAJAR MALINGPING - Damanhuri, Damanhuri; Rahman Hakim, Zerri; Andriana, Encep; Trianingsih, Alfiani (LPPM Universitas Bina Bangsa, 2024)
This study aims to determine the learning outcomes of Civics between students who use the picture and picture cooperative learning model and students who use conventional learning models. Quantitative research is a quasi-experimental type. The population in this study were all fourth grade students at SDN Kadujajar Malingping, while the sample in this study was class IVA as an experimental class which was treated using a picture and picture cooperative learning model and class IVB as a control class which was treated using a conventional learning model. . The study results showed that tcount > ttable or 8.09 > 1.996 so it can be concluded that there is a difference between the learning outcomes of the experimental class and the control class on the final test (posttest). With an average value of 78.77 the average value for the experimental class and 61.44 the average value for the control class. With an average value of 89.14 the average value for the experimental class and 83.16 the average value for the control class.